Role of Antidepressants in Acute Coronary Syndrome: An Evidence-Based Case Report - Hamzah Shatri; Nabella Qisthina Laksita Dewi; Vinandia Irvianita; Edward Faisal; Rudi Putranto (Acta Medica Indonesiana)
Background: Acute coronary syndrome (ACS) and depression are related to each other. Detection and proper treatment of these conditions can improve functional ability and quality of life. However, there is still controversy in this population regarding the use, safety, and efficacy of antidepressant pharmacotherapy. This evidence-based case report (EBCR) aims to determine the role of antidepressants in acute coronary syndrome patients. Methods: Literature searching was performed using online databases such as EBSCO, Embase, PubMed, ClinicalKey, and ScienceDirect according to clinical questions. The studies were selected based on the suitability of the inclusion and exclusion criteria followed by critical appraisal. Results: In patients with ACS, antidepressants do not affect mortality but may reduce rehospitalization. In patients with ACS and depression who received antidepressants, there is a reduced risk of myocardial infarction (MI) recurrence. In post-ACS patients, the use of antidepressants is associated with a reduced risk of recurrent MI. Conclusion: In ACS patients, antidepressants do not affect mortality, but can reduce the incidence of myocardial reinfarction.